Manutan dan percaya klenik: Mengulik agreeableness dan superstitious belief pada masyarakat Jawa Tengah - Prabaswara, Yehuda Ananta; Muhammad, Amri Hana (Fakultas Psikologi Universitas Hang Tuah, 2024)
Superstitious belief is a belief or trust in a certain event, activity, or item that is believed to have a good or bad impact in the future through an irrational mechanism. On the other hand, agreeableness is a personality dimension characterized by cooperative characteristics, easily trusting others, and having a tendency to avoid conflict. This study aims to determine the relationship between agreeableness and superstitious beliefs in Central Javanese society. The research participants were Javanese people living in Central Java aged 18-60 years, as many as 217 people selected through purposive sampling. Data collection was carried out using the BFI-2 (Big Five Inventory) scale and the superstitious belief scale developed based on aspects of superstitious belief. The results showed a weak negative correlation. This finding provides information that other factors may be more dominant in predicting superstitious belief